The Immune System, Immunity and Immune Logics: Troubling Fixed Boundaries and (Re)conceptualizing Relations (Medicine Anthropology Theory, 2024)
Special issue 'The Immune System, Immunity and Immune Logics: Troubling Fixed Boundaries and (Re)conceptualizing Relations', guest edited by Andrea Ford and Julia Swallow.